Effect of the combination of acupuncture based on Yuan-Luo Da-Jie-Jing and repetitive transcranial magnetic stimulation on type 1 complex regional pain after stroke: a randomized controlled trial protocol - Liu, Huan; Zhang, Xin-yuan; Hong, Kun; Gao, Juan (Frontiers in Neurology, 2025)
BackgroundStroke is a major cause of death and disability worldwide. Approximately 12–25% of stroke survivors develop complex regional pain syndrome type I (CRPS-I) within 3–12 months. CRPS-I is characterized by severe limb pain, abnormal pain, and vasomotor instability, which hinders rehabilitation. Insufficient efficacy and adverse reactions limit the use of current pharmacological treatments, such as non-steroidal anti-inflammatory drugs and gabapentinoids. Post-stroke CRPS-I is characterized by neuroinflammation, maladaptive neural plasticity, and central/peripheral sensitization. Repetitive transcranial magnetic stimulation (rTMS) regulates pain through cortical reorganization and inhibition of neuroinflammation, while acupuncture, particularly the Yuan-Luo Dajiejing (YLDJJ) technique, reduces central sensitization by activating endogenous opioids. However, no randomized controlled trial has compared the efficacy of YLDJJ acupuncture combined with rTMS in the treatment of CRPS-I after stroke.MethodsThis randomized controlled trial will randomly assign eligible participants to three groups in a 1:1:1 ratio: the experimental group (YLDJJ acupuncture + rTMS), the control group 1 (conventional acupuncture + rTMS), and the control group 2 (sham acupuncture + rTMS). The participants will be aged 18–80 years old, with CRPS-I developing after stroke and meeting the specific inclusion criteria. The intervention measures will be administered once daily for 20 days. Pain intensity, assessed using the visual analogue scale (VAS), will be measured at baseline, on days 10 and 20, and at 1 and 3 months after treatment completion. Secondary outcome measures include motor function, muscle tone, shoulder range of motion, activities of daily living, thermal asymmetry, and neuroplasticity-related indicators. The sample size will be 126 participants, accounting for a 20% dropout rate.ConclusionThis trial will evaluate the efficacy and safety of Yuan-Luo Da-Jie-Jing acupuncture combined with rTMS. The results will be compared to two control groups: one receiving conventional acupuncture with rTMS, and the other receiving sham acupuncture with rTMS. The results are expected to provide evidence for formulating clinical treatment strategies for CRPS-I after stroke.Clinical trial registration(ITMCTR, http://itmctr.ccebtcm.org.cn/), No. ITMCTR2025001677.